Gut microbial dysbiosis in patients with Cushing’s disease in long-term remission. Relationship with cardiometabolic risk - Valassi, Elena; Manichanh, Chaysavanh; Amodru, Vincent; Fernández, Pedro González; Gaztambide, Sonia; Yañez, Francisca; Martel-Duguech, Luciana; Puig-Domingo, Manel; Webb, Susan M. (Frontiers in Endocrinology, 2023)
Patients with Cushing’s disease (CD) in remission maintain an increased cardiovascular risk. Impaired characteristics of gut microbiome (dysbiosis) have been associated with several cardiometabolic risk factors. Twenty-eight female non-diabetic patients with CD in remission with a mean (±SD) age of 51±9 years, mean (±SD) BMI, 26±4, median (IQR) duration of remission, 11(4) years and 24 gender-, age, and BMI-matched controls were included. The V4 region of the bacterial 16S rDNA was PCR amplified and sequenced to analyse microbial alpha diversity (Chao 1 index, observed number of species, Shannon index) and beta diversity analysis through the Principal Coordinates Analysis (PCoA) of weighted and unweighted UniFrac distances. Inter-group difference in microbiome composition was analysed using MaAsLin2. The Chao 1 index was lower in CD as compared with controls (Kruskal-Wallis test, q = 0.002), indicating lower microbial richness in the former. Beta diversity analysis showed that faecal samples from CS patients clustered together and separated from the controls (Adonis test, p<0.05). Collinsella, a genus form of the Actinobacteria phylum was present in CD patients only, whereas Sutterella, a genus from Proteobacteria phylum, was scarcely detectable/undetectable in CD patients as well as Lachnospira, a genus of the Lachnospiraceae family of the Firmicutes phylum. In CS, the Chao 1 index was associated with fibrinogen levels and inversely correlated with both triglyceride concentrations and the HOMA-IR index (p<0.05). Patients with CS in remission have gut microbial dysbiosis which may be one of the mechanisms whereby cardiometabolic dysfunctions persist after “cure”.